Numerical Analysis of Thermal Impact between the Cooling Facility and the Ground - Paweł Sokołowski; Grzegorz Nawalany; Tomasz Jakubowski; Ernest Popardowski; Vasyl Lopushniak; Atilgan Atilgan (Energies, 2022)
The article presents the results of research on the range of the impact of a cooling facility on the surrounding ground. An analysis of the heat exchange with the ground and through the building partitions was carried out. The analysis was carried out on the basis of the results of actual field tests carried out throughout the measurement year. The object of the research was an agricultural cold store located in southern Poland. The computational analysis of the interaction between the cooling facility and the ground was based on the numerical elementary balances method. The validation of the calculation model was performed based on the adopted boundary conditions. Calculations for the analyzed variants were carried out on the basis of a geometric model of the cooling facility built in the WUFI®plus program, corresponding to the actual dimensions. The analysis of the energy balance of the studied facility showed that the share of energy flow through the floor to the ground constitutes 8.2% of all energy flows through other partitions and the ventilation system. In order to maintain the set air temperature inside the studied building, intensive cooling was required with an energy demand of 5184.5 kWh/year. The results of the research showed that the range of the thermal impact of the building changes depending on the location of the studied ground area in terms of cardinal direction. The external and internal microclimate characteristics also affect the extent of the impact of the cooling facility on the surrounding ground. Under the assumption of stable values of Θi within a range of 0.0–4.0 °C, the largest range of influence (4.0 m) occurs in the summer.